5 - La nouvelle économie politique en Afrique : une analyse des enjeux *: DOI: 10.4314/ad.v31i1.22252 - Ateba, Étienne Modeste Assiga (Africa Development, 2006)
The purpose of the present article is to analyse in the context of less democratic political systems the stakes – in terms of equitable revenue repartition – of the political economy of structural reforms which are still pervasive in Africa, especially in the line of what is currently designed as the ‘policy of the “second generation” of reforms’. In this respect, the hypothesis developed in this study is that the State is confronted with second order constraints in its relations with both national and international organisations and the markets, the reason being that strategic behaviours of economic agents do not necessary converge towards an optimal Nash equilibrium. These divergences affect growth and development of Sub-Saharan African countries so that such an equilibrium seems rather difficult to reach. To overcome it, the State could play a decisive role by introducing competition in order to increase the organisational efficiency of the economy, however the pertinence of this competition still has to be proved in Africa.